Sosialisasi Edukasi Maggot BSF Sebagai Pengurai Sampah Organik Di Kelurahan Anggut Dalam - Aprianti Lubis; Fadhiil Ahmadi; Entin Oktantia Safitri; Glori Pesta Pince Sitorus; Refo Elfianza; Muhammad Fikri; Ulfiyah Mei; Yulanda Nurul Fadhila; Hafidza Zia (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Kelurahan Anggut Dalam is one of the densely populated areas in Bengkulu City that faces challenges in managing organic waste, primarily due to the increasing activities of households and small-scale traders. One innovative and sustainable solution is the utilization of maggots from the Black Soldier Fly (BSF) as organic waste decomposers. This study aims to raise public awareness and knowledge through environmental education activities based on BSF maggot cultivation. The methods used include field observations, public outreach, technical training, and evaluation of community understanding. The results show that after the educational activities were implemented, there was a significant increase in residents' understanding of organic waste management and the economic potential of maggot cultivation. The program also successfully reduced the volume of household organic waste in several neighborhood units (RT). BSF-based environmental education has proven to be an effective participatory approach to support clean environment initiatives and integrated waste management.